Kinerja Pemerintah Kabupaten Nias Utara Dari Sudut Rasio Laporan Keuangan - Siahaan, Marta Nurfiza; Purba, Sahala; Pasaribu, Prengki Sahat Tua; Saragih, Yogi Natalis; Gea, Joni Kurniawan (Journal of Innovation in Management, Accounting and Business, 2024)
The purpose of measuring the performance of local government financial management is to improve government performance, but performance measurement will help improve the ultimate effectiveness of local financial management. This research is a quantitative descriptive research with the research subject of local government financial information in 2013-2022, and the research object of district PAD revenue. The data collection technique is documentation collection. The calculation results of the existing ratios show that the financial independence ratio of North Nias Regency is very low at 5%. The ratio of Regional Financial Dependence is high at 87%. The ratio of the degree of regional fiscal decentralization is low at 3%. The PAD effectiveness ratio is quite effective at 97%. The PAD efficiency ratio is quite effective at 3%. The local tax effectiveness ratio is less effective at 86%. The local tax efficiency ratio is very efficient at 3%. The ratio of the degree of contribution of BUMD in North Nias Regency contributes an average value of 6%. Based on the analysis of the report that North Nias Regency 2013-2022 can be stated in general that North Nias Regency is not good enough in financial implementation and management.